Piecing together our woodlands – Interview with Suzanne Prober. (5th September 2018) - McDonald, Tein; Prober, Suzanne M.
Summary: Over nearly three decades, Suzanne Prober has played a pivotal role in shifting research in Australian agricultural landscapes to include a focus on native woodlands, and to examine ways woodland conservation can co‐exist with production, contributing to new models for conservation within multi‐use landscapes.